ACTIVATION AND EFFECTIVE USE OF THE INDUSTRIAL ENTERPRISE INTELLECTUAL POTENTIAL - Островська, Галина (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2020)
The article examines the problem of the enterprise intellectual potential activation and use. Organizational problems in the field of Ukrainian industrial enterprises human capital are outlined. Accented on the key importance of staff intellectualization as a basis for its intensive (qualitative) development. Restrictions on the application of traditional management approaches to employees were identified. The role of individual and group learning as a necessary condition for activation and effective use of the enterprise intellectual potential was highlighted. The basic principles were highlighted, and methods of personnel management necessary for ensuring the successful operation of the enterprise were developed. Environmental factors, internal factors, constrictions and barriers in the context of effective use of the enterprise intellectual potential were analyzed. The list of indicators that create an impact of intellectual employees innovative activity level has been supplemented. The conclusion that the enterprise should improve the corporate structure is substantiated, because it creates conditions for more effective activity of intellectual employees and accelerated transition of the enterprise to an innovative model of development. The toolkit of activization and effective use of intellectual potential of modern enterprises is developed. A number of organizational and economic measures for maintenance of positive development dynamics and effective use of the enterprise intellectual potential in the course of innovations introduction were offered Scientific novelty of research is to improve the methodological approach in the context of activation and effective use of the industrial enterprise intellectual potential, which determines the implementation of management functions according to organizational environment formation and evaluation stages. The obtained results form the basis of the organizational and economic mechanism for ensuring the effective use of intellectual potential in industrial enterprises conditions.